Proteomics to predict relapse in patients with myelodysplastic neoplasms undergoing allogeneic hematopoietic cell transplantation - Guru Subramanian Guru Murthy; Tao Zhang; Yung-Tsi Bolon; Stephen Spellman; Jing Dong; Paul Auer; Wael Saber (BMC, 2024)
Abstract Disease relapse remains a major barrier to success after allogeneic hematopoietic cell transplantation (allo-HCT) in myelodysplastic neoplasms (MDS). While certain high risk genomic alterations are associated with increased risk of relapse, there is a lack of clinically applicable tools to analyze the downstream cellular events that are associated with relapse. We hypothesized that unique proteomic signatures in MDS patients undergoing allo-HCT could serve as a tool to understand this aspect and predict relapse. Using the Center for International Blood and Marrow Transplant Research (CIBMTR) database, we identified 52 MDS patients who underwent allo-HCT and analyzed their proteomic profile from pretransplant blood samples in a matched case-control design. Twenty-six patients without disease relapse after allo-HCT (controls) were matched with 26 patients who experienced relapse (cases). Proteomics assessment was conducted using the Slow Off-rate Modified Aptamers (SOMAmer) based assay. In gene set enrichment analysis, we noted that expression in the hallmark complement, and hallmark allograft rejection pathways were statistically enriched among patients who had disease relapse post-transplant. In addition, correlation analyses showed that methylation array probes in cis- and transcription regulatory elements of immune pathway genes were modulated and differentially sensitize the immune response. These findings suggest that proteomic analysis could serve as a novel tool for prediction of relapse after allo-HCT in MDS.